1999
DOI: 10.1046/j.1365-2311.1999.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between plant traits and herbivore attack: a study of a stem galling midge in the neotropics

Abstract: Summary 1. The relationship between plant traits and the frequency of attack by a stem galling midge, Neolasioptera sp. (Diptera: Cecidomyiidae), on Eremanthus erythropappus (Asteraceae) was studied. The morphological changes of the host after a galler attack and the potential effects of these changes on attacks by the next generation of gallers were analysed. The study was conducted in the Serra do Japi, São Paulo, south‐eastern Brazil. 2. Galled branches were significantly longer, thicker, and had more leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
(48 reference statements)
0
22
1
Order By: Relevance
“…The effect of herbivores on plant growth and productivity has been previously reported (Owen 1980;Abrahamson & Weis 1987). Some studies showed that previously galled branches were longer and bore more leaves and shoots than non-galled branches (Fernandes & Ribeiro 1990;Prado & Vieira 1999). The effect of gall-inducing insects on plant structural complexity and biomass, or vice versa, can only be tested by manipulative experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of herbivores on plant growth and productivity has been previously reported (Owen 1980;Abrahamson & Weis 1987). Some studies showed that previously galled branches were longer and bore more leaves and shoots than non-galled branches (Fernandes & Ribeiro 1990;Prado & Vieira 1999). The effect of gall-inducing insects on plant structural complexity and biomass, or vice versa, can only be tested by manipulative experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The Plant Vigor Hypothesis (PVH; Price 1991) predicts that insect herbivores will choose preferentially large, more vigorously growing plants or plant modules and that offspring performance will be greater on these more vigorous plants or plant modules. Its predictions have been widely tested in diverse ecosystems around the world, being either fully supported (Price et al 1987a, b;Craig et al 1989;Kimberling et al 1990; Price and Ohgushi 1995;Stein and Price 1995;Woods et al 1996;Carr et al 1998;Inbar et al 2001;de Bruyn et al 2002), partially supported (Cornelissen et al 1997;Prado and Vieira 1999;Cornelissen and Fernandes 2001c;Fritz et al 2000;Ferrier andPrice 2004), or refuted (de Bruyn 1995;Faria and Fernandes 2001;Rehill and Schultz 2001). Faria and Fernandes (2001) argued that the amount of resources has been generally underestimated in large size class shoots.…”
Section: Introductionmentioning
confidence: 99%
“…Although the oviposition preference of subsequent generations was not measured, they suggest that a preference for vigorous growth could result in resource regulation. Prado and Vieira (1999) found that the stem-galling midge, Neolasioptera sp., that induces galls on a small tree Eremanthus erythroppapus in Brazil, produced more galls on longer, thicker branches and that these branches had more galls in subsequent years. The aggregation of currentand previous-year galls on vigorously growing shoots is consistent with the resource regulation hypothesis, with galls increasing the rate of shoot growth and increasing subsequent galling.…”
Section: Resource Regulation By Resource Manipulationmentioning
confidence: 99%